Effect of bio-based lubricant towards emissions and engine breakdown due to spark plug fouling in a two-stroke engine. (1st June 2019) - Zulfattah, Z.M.; Zulkifli, N.W.M.; Masjuki, H.H.; Harith, M.H.; Syahir, A.Z.; Norain, I.; Jumaidin, R.; Yusoff, M.N.A.M.; Alwi, Azham; Jamshaid, M.; Arslan, A.
Abstract: Two-stroke also known as two-cycle gasoline engine is a spark ignition engine. Its uniqueness to the four-stroke engine is that this engine does not require lubricant sump, which makes construction lightweight and simple. Its lubricant is mixed with gasoline and burnt together during combustion. There are reports which stated that higher spark plug fouling is due to carbon deposition on the spark plug electrodes on a two-stroke engine when compared to the four-stroke. While many factors could have affected this situation, however, in this paper, the effect of mineral and bio-based lubricants towards carbon deposition and emissions are studied and reported. Idle, half and full throttle operation modes had been conducted on a two-stroke, 43 cubic centimeter engine. To keep combustion temperature below self-cleaning temperature on all three modes of operation, a zero-load test was utilized. This situation accelerates the deposition process as low temperature causes incomplete combustion. This could lead to the accumulation of char, unburned fuel, as well as condensed water and acids as the by-products blanket the spark plug electrodes and the exhaust system. Five samples had been prepared with a commercially available mineral lubricant (T0) as reference. Trimethylolpropane Trioleate, TMPTO derived from plant origin was used as the bio-based candidate. It was then mixed with T0 which created another four lubricant samples namely T10, T15, T20 and T50 with 10%, 15%, 20% and 50% TMPTO accordingly. Results show that mineral lubricant T0 delivers the lowest hydrocarbon HC, carbon monoxide CO and smoke opacity during idle and half throttle operations. However, it exhibits a greasy deposit on the spark plug circumference and dry carbon deposits on its insulator tip. T0 also emits a liquid residue at the exhaust manifold. T10 and T50 show a wet deposit blanketing both electrodes. Severe deposition was recorded by T50 that caused the engine to fail half way with its emissions had the worst recording. T15 and T20 exhibit only dry carbon deposition on the spark plug circumference. However, T20 has outperformed T15 in terms of emissions with lower CO and CO2 emissions during idling and half-throttling. With better emissions than T15 and better carbon deposition than mineral (T0), T20 could be proposed to be used as a commercial two-stroke lubricant. Graphical abstract: Image 1 Highlights: TMPTO blends burns cleaner in the combustion chamber compares to mineral lubricant. No unburnt lubricant observed. Spark plug fouling is harder to occur. Mineral lubricant emits unburnt liquid lubricant at the exhaust manifold. This liquid will pollute water and soil once in contact. TMPTO blends inherit flash temperature and viscosities at par with standard lubricant. Blending of TMPTO with mineral lubricant produces homogeneous mixture. T20 blend emits significantly low CO emission during idling and half throttling. This ratio could be proposed to substitute the mineral part in the commercial lubricant.